Perancangan Aplikasi Koperasi Sekolah Pada SMPN 9 Depok Berbasis Desktop - Khoirunnisa, Khoirunnisa; Susanti, Lia (Universitas Indraprasta PGRI Jakarta, 2024)
The School Cooperative at SMP Negeri 9 Depok plays an important role in providing students with various essential items, such as stationery and food, while also serving as a platform for students to gain entrepreneurial experience. In the digital era, implementing information technology through a cooperative application is crucial to enhance transparency and accountability in managing transactions and inventory. Currently, SMPN 9 Depok lacks an application-based system for sales, relies on manual record-keeping, faces difficulties in monitoring reports, and experiences slow adaptation to technology.The purpose of this study is to implement a Java-based system that collects and processes data through an application with a user-friendly interface. The research employs the Software Development Life Cycle (SDLC) method, specifically using the Waterfall model. Key features developed include inventory management, transaction recording, and financial reporting. With this application, transaction processes are automatically recorded, allowing cooperative data to be managed more accurately and efficiently. Trial results show that this application improves the speed and accuracy of transaction records within the school cooperative, reducing manual errors and facilitating report generation. This application is expected to be an effective solution for managing the cooperative at SMPN 9 Depok and could potentially be applied to other school cooperatives as well.